2016
DOI: 10.1186/s13063-016-1207-6
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to improve patients’ compliance with therapies aimed at lowering glycated hemoglobin (HbA1c) in type 1 diabetes: systematic review and meta-analyses of randomized controlled clinical trials of psychological, telecare, and educational interventions

Abstract: BackgroundBrazilian records on glycemic control in patients with type 1 diabetes show treatment efficacy. Poor patient adherence to therapeutic proposals influences these results and can be associated with social, psychological, and economic aspects, besides others factors. The aim of this study was to evaluate the efficacy of psychological, telecare, and educational interventions to improve treatment compliance among patients with type 1 diabetes. Compliance was assessed indirectly using reduction of glycated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 49 publications
0
62
0
7
Order By: Relevance
“…The reviews of de Jongh et al [24] and Viana et al [49] were both weighted 2 stars. The former focused on mobile messaging interventions, including medication reminders, and found no improvement in hemoglobin A 1c (HbA 1c ) compared with usual care in a meta-analysis of 2 RCTs [24].…”
Section: Resultsmentioning
confidence: 99%
“…The reviews of de Jongh et al [24] and Viana et al [49] were both weighted 2 stars. The former focused on mobile messaging interventions, including medication reminders, and found no improvement in hemoglobin A 1c (HbA 1c ) compared with usual care in a meta-analysis of 2 RCTs [24].…”
Section: Resultsmentioning
confidence: 99%
“…The results of these studies indicate that family‐based, behavioral procedures such as goal‐setting, problem solving, self‐monitoring, positive reinforcement, behavioral contracts, supportive parental communications, family restructuring, and appropriately shared responsibility for diabetes management have improved regimen adherence and glycemic control . In addition, these interventions have improved the parent‐adolescent relationship, and improved regimen adherence . Studies of behavioral family systems therapy with diabetes‐specific tailoring targeting diabetes‐specific behavioral problems, and training in behavioral contracting techniques have shown improvements in family conflict and regimen adherence as well as improved glycemic control over 18 months .…”
Section: Psychosocial and Behavioral Interventionsmentioning
confidence: 99%
“…Previous systematic reviews of the literature and meta-analysis [174][175][176] indicate that a number of controlled studies have shown the efficacy of psychosocial and behavioral interventions for children and adolescents with diabetes, although this literature is not without some methodological limitations. 4,5,174,[177][178][179][180] Most of these interventions have included the family as an integral part of treatment.…”
Section: Psychosocial and Behavioral Interventionsmentioning
confidence: 99%
“…A variety of educational and behavioural interventions for adolescents with Type 1 diabetes have demonstrated some benefit in terms of glycaemic control; however, the feasibility of incorporating such interventions into clinical practice may be limited by healthcare resources and time, thus limiting scalability [3][4][5][6][7]. Text-messaging interventions have been studied in young people with Type 1 diabetes, and remain a practical and promising strategy [8][9][10].…”
Section: Introductionmentioning
confidence: 99%